The moon - Landau, Elaine (New York : Children's Press, 2008)
Provides facts about the moon, discussing how far it is from Earth, its orbit, and gravity, explaining the phases of the moon, describing conditions on the moon, and reviewing the history of missions to the moon.
Meet the moon -- Phases of the moon -- A different world -- Moonscape -- Going to the moon.
Includes bibliographical references (p. 44-45) and index.
School Library Journal.
4.4
3-6
Keywords: Moon -- Juvenile literature; Moon; Moon